The EFFECT OF COMBRETUM INDICUM LEAVES ON LIPID PROFILE AND HEMATOLOGY OF MICE INDUCED WITH ALLOXAN - Rahayu, Sekar; Aryani, Retno; Rosadi, Imam; Nugroho, Rudy Agung (Universitas Medan Area, 2024)
Diabetes has become one of the main causes of death throughout the world recent years. Diabetes symptoms include high blood glucose and hyperlipidemia. An rise in blood glucose can produce an increase in the amount of leukocytes and erythrocytes in the hematology profile. Consequently, this study was to ascertain how extract Combretum indicum leaves affected the lipid profile and hematological of mice given alloxan. The study sample included 36 male mice divided into six groups: normal control (KN) without treatment, negative control (K-) with alloxan treatment, positive control (K+) with alloxan and glibenclamide treatment, P1 with alloxan treatment and Combretum indicum extract dose 100 mg/kgBW, P2 with alloxan treatment and Combretum indicum extract dose 200 mg/kgBW, and P3 with alloxan treatment and Combretum indicum extract dose 400 mg/kgBW. After the mice hyperglycemia on day 3rd, the therapy was continued. The treatment lasted for 20 days. On days 10 and 20, hematological and lipid profile measures were performed. Combretum indicum leaves have the ability to lower total cholesterol, LDL and triglyceride with ascalate HDL levels on 20 days of treatment. In addition, it markedly raised the percentage of lymphocytes and neutrophils with escalate the quantities of lymphocytes and neutrophils in alloxan induced mice. So, in aloxan-induced mice, this extract can reduce the effects of diabetes.